Study of the Partial Substitution of Pb by Sn in Cs–Pb–Sn–Br Nanocrystals Owing to Obtaining Stable Nanoparticles with Excellent Optical Properties - Vitoreti, Ana Beatriz Ferreira (J Phys Chem C Nanomater Interfaces, 2018)
[Image: see text] Halide perovskites are revolutionizing the photovoltaic and optoelectronic fields with outstanding performances obtained in a remarkably short time. However, two major challenges remain: the long-term stability and the Pb content, due to its toxicity. Despite the great effort carried out to substitute the Pb by a less hazardous element, lead-free perovskite still remains more unstable than lead-containing perovskites and presents lower performance as well. In this work, we demonstrate the colloidal preparation of Cs–Pb–Sn–Br nanoparticles (NPs) where Sn is incorporated up to 18.8%. Significantly, we have demonstrated that the partial substitution of Pb by Sn does not produce a deleterious effect in their optical performance in terms of photoluminescence quantum yield (PLQY). We observed for the first time a positive effect in terms of enhancement of PLQY when Sn partially substitutes Pb in a considerable amount (i.e., higher than 5%). PLQYs as high as 73.4% have been obtained with a partial Pb replacement of 7% by Sn. We present a systematic study of the synthesis process in terms of different growth parameters (i.e., precursor concentration, time, and temperature of reaction) and how they influence the Sn incorporation and the PLQY. This high performance and long-term stability is based on a significant stabilization of Sn(2+) in the NPs for several months, as determined by XPS analysis, and opens an interesting way to obtain less Pb-containing perovskite NPs with excellent optoelectronic properties.